Integration of information and communication technology in teaching English among in-service teachers - Peng Ran; Rafiza Abdul Razak; Siti Hajar Halili (Institute of Advanced Engineering and Science, 2024)
The widespread application of information and communications technology (ICT) in the field of education has drawn criticism. This investigation was to discover factors influencing English language teaching (ELT) in-service teachers’ integration of ICT. The sample consists of 1216 in-service teachers who teach English language in China. Four factors are found to influence ELT in-service teachers’ integration of ICT: attitudes, self-efficacy, digital competence, and digital tools use. The findings of the research utilizing the partial least squares structural equation modeling (PLS-SEM) approach demonstrated that all four criteria have a substantial impact on how ICT is integrated by ELT in-service teachers. By considering all the variables that affect ELT in-service instructors, this research offered helpful insights for an effective designs of English language teaching with ICT.